Preparation of iron oxide silica particles for Zika viral RNA extraction - Alex H.F. Lee; Steven F. Gessert; Yutao Chen; Nikolay V. Sergeev; Babak Haghiri (Heliyon, 2018)
In this work, a robust synthetic pathway for magnetic core preparation and silica surface coating of magnetic microparticles is presented. Silica-coated magnetic particles are widely used to extract DNA and RNA from various biological samples. We present a novel route for the synthesis of iron oxide silica particles (Fe3O4@Silica) and demonstrate their performance for extracting ZIKA viral RNA from serum. The iron (II, III) oxide (Fe3O4), magnetite core is first prepared by ammonia neutralization of ferrous and ferric chloride aqueous solution under argon, followed by the addition of citrate salt to stabilize the surface of the resultant magnetic nanospheres. After this one-pot, two-step synthesis, the magnetic nanospheres are consumed during silica coating by hydrolysis of tetraethoxysilane (TEOS) under alkaline condition. The final product is a sphere-like magnetic aggregate with a size range of 1–2 micron. By simply suspending the magnetic aggregates in guanidinium chloride solution, the silica surface can be prepared for RNA binding. The RNA extraction efficiency was evaluated by extracting ZIKA viral RNA from serum followed by a PCR-based assay. The data indicate excellent recovery of target RNA and removal of PCR inhibitors. This manufacturing procedure for the silica coated microparticles provides a low-cost, effective and ready for scale-up method whose performance is equivalent to commercial alternatives such as magnetic silica surface particles for DNA and RNA sample preparations. The cost of the clinical assays could be largely decreased due to the 100 fold reduction in cost by replacing the commercially available magnetic particles with the developed material for RNA extraction.